Determining Clinically Meaningful Thresholds for the Hip Outcome Score Sport-Specific Subscale in Athletes Undergoing Hip Arthroscopy for Femoroacetabular Impingement Syndrome. Issue 11 (September 2022) - Owens, Jade S.; Jimenez, Andrew E.; Lee, Michael S.; George, Tom; Maldonado, David R.; Domb, Benjamin G.
Background: The minimal clinically important difference (MCID), Patient Acceptable Symptom State (PASS), substantial clinical benefit (SCB), and maximum outcome improvement (MOI) satisfaction threshold for the Hip Outcome Score Sport-Specific Subscale (HOS-SSS) have not been established in athletes undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS). Purpose: To determine threshold MCID, PASS, SCB, and MOI satisfaction threshold values for the HOS-SSS in athletes undergoing hip arthroscopy for FAIS at minimum 2–year follow–up. Study Design: Cohort study (Diagnosis); Level of evidence, 3. Methods: Anchor questions were administered to recreational, organized amateur, high school, college, and professional athletes who underwent primary hip arthroscopy for FAIS between May 2015 and March 2019. Patients were included if they were younger than 50 years, answered the anchor questions, and had preoperative and minimum 2–year follow–up for the HOS-SSS, modified Harris Hip Score (mHHS), Non-Arthritic Hip Score (NAHS), and visual analog scale (VAS) for pain. Exclusion criteria were Tönnis grade >1, hip dysplasia (lateral center–edge angle <18°), and previous ipsilateral hip surgery or conditions. Receiver operating characteristic (ROC) analysis was used to determine PASS, SCB, and MOI satisfaction for the HOS-SSS. Two distribution methods were used to calculate MCID for HOS-SSS. Results: A total of 225 athletes who underwent primary hip arthroscopy met the inclusion criteria. Of those athletes, 200 (88.9%) who had minimum 2–year follow–up and information regarding return to sport (RTS) were included. The cohort included 124 (62.0%) women and 76 (38.0%) men with a mean ± standard deviation age of 29.4 ± 10.4 years, body mass index of 25.6 ± 5.4, and follow–up of 29.5 ± 5.1 months. Athletes experienced significant improvements in HOS-SSS, mHHS, NAHS, and VAS from preoperative to latest postoperative follow–up ( P < .001), and mean satisfaction was 8.2. The RTS rate was 83.7%. ROC analysis determined that the PASS, MOI satisfaction threshold, SCB absolute score, SCB change score, and MCID (baseline/change score methods) for the HOS-SSS were 77.0, 44.6%, 92.7, 30.6, and 10.6, respectively, with athletes achieving thresholds at high rates (80.0%, 80.5%, 45.0%, 54.0%, and 79.5%, respectively). Conclusion: This study identified values for the HOS-SSS that can be used to define clinically meaningful outcomes in athletes after primary hip arthroscopy for FAIS. The PASS, MOI satisfaction threshold, SCB absolute score, SCB change score, and MCID for the HOS-SSS at minimum 2–year follow–up in athletes after primary hip arthroscopy were 77.0, 44.6%, 92.7, 30.6, and 10.6, respectively.